2019
DOI: 10.1177/2040622319851640
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α inhibitors in the treatment of hidradenitis suppurativa

Abstract: Hidradenitis suppurativa (HS) is a complex disease with a dramatic impact on the quality of life of patients that it afflicts. Despite this, there are few treatment options offering long-term relief. The exact pathophysiology of HS is unclear, although the current theory involves follicular obstruction, rupture, and subsequent inflammation leading to fistula and abscess development in intertriginous skin. Several inflammatory modulators have been implicated in the development of HS, including tumor necrosis fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 77 publications
(130 reference statements)
1
40
0
4
Order By: Relevance
“…TNF-a is a highly pleiotropic proinflammatory cytokine, playing essential roles especially in tissue immune cell infiltration, T-cell functional polarization, systemic inflammation, and metabolic alterations, all being relevant to HS (Beutler and Cerami, 1989). TNF-a inhibition has been demonstrated to modulate T helper (Th) 17 activity (Jiménez-Gallo et al, 2018), and the use of TNF-a inhibitors (such as Adalimumab and Infliximab) demonstrate clinical efficacy in clinical trials (Savage et al, 2019).…”
Section: Tnf-amentioning
confidence: 99%
“…TNF-a is a highly pleiotropic proinflammatory cytokine, playing essential roles especially in tissue immune cell infiltration, T-cell functional polarization, systemic inflammation, and metabolic alterations, all being relevant to HS (Beutler and Cerami, 1989). TNF-a inhibition has been demonstrated to modulate T helper (Th) 17 activity (Jiménez-Gallo et al, 2018), and the use of TNF-a inhibitors (such as Adalimumab and Infliximab) demonstrate clinical efficacy in clinical trials (Savage et al, 2019).…”
Section: Tnf-amentioning
confidence: 99%
“…TNF-α levels exhibited a positive correlation with HS severity and the therapeutic efficacy of TNF-α inhibitors supports the role of the dysregulated production of these cytokines in the pathophysiology of HS [ 77 , 78 ]. The only Food and drug administration-approved drug available to treat HS is adalimumab, a monoclonal antibody targeting TNF-α.…”
Section: Resultsmentioning
confidence: 82%
“…Two large double-blind, placebo-controlled, randomized clinical trials (RCTs), PIONEERI and II, demonstrated the safety and efficacy of adalimumab. In these studies, patients received either adalimumab (160 mg at week 0, 80 mg at week 2, and 40 mg weekly starting at week 4) or placebo for 12 weeks [ 78 , 110 ]. The primary endpoint in both studies was the number of patients achieving clinical response according to the Hidradenitis Suppurativa Clinical Response (HiSCR) at week 12 defined as a 50% decrease in total abscess and inflammatory nodule lesions from baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Little data on HS treated with certolizumab pegol have been published. 6,7 Certolizumab pegol offers an alternative for other anti-TNFinhibitors in pregnant patients, due to its inability to cross the placenta, 8 which to our knowledge has only been examined in a single patient. 9 Our literature review identified only a single retrospective study by Sand et al 7 on off-label use of TNF-inhibitors, which showed no efficacy from certolizumab pegol in two patients earlier treated with infliximab and adalimumab, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Little data on HS treated with certolizumab pegol have been published 6,7 . Certolizumab pegol offers an alternative for other anti‐TNF‐inhibitors in pregnant patients, due to its inability to cross the placenta, 8 which to our knowledge has only been examined in a single patient 9 .…”
Section: Discussionmentioning
confidence: 99%